Catchment scale deforestation increases the uniqueness of subtropical stream communities - Schneck, Fabiana; Bini, Luis M.; Melo, Adriano S.; Petsch, Danielle K.; Saito, Victor S.; Wengrat, Simone; Siqueira, Tadeu [UNESP] (Springer Nature, 2022)
Local communities and individual species jointly contribute to the overall beta diversity in metacommunities. However, it is mostly unknown whether the local contribution (LCBD) and the species contribution (SCBD) to beta diversity can be predicted by local and regional environmental characteristics and by species traits and taxonomic relatedness, respectively. We investigated the LCBD and SCBD of stream benthic diatoms and insects along a gradient of land use intensification, ranging from streams in pristine forests to agricultural catchments in southeast subtropical Brazil. We expected that the LCBD would be negatively related to forest cover and positively related to the most unique streams in terms of environmental characteristics and land use (hereafter environmental and land use uniqueness, respectively). We also expected that species with a high SCBD would occur at sites with reduced forest cover. We found that the LCBD of diatoms and insects was negatively related to forest cover. The LCBD of insects was also positively related to environmental and land use uniqueness. As forest cover was negatively related to uniqueness in land use, biologically unique streams were those that deviated from the typical regional land cover. We also found that diatom traits, insect traits, and taxonomic relatedness partly explained SCBD. Furthermore, the SCBD of diatoms was positively correlated with forest cover, but the inverse was found for insects. We showed that deforestation creates novel and unique communities in subtropical streams and that species that contribute the most to beta diversity can occur at opposite ends of a land use gradient.
Keywords: Aquatic insect; Diatom; LCBD; Metacommunity; Trait